Preparation method and application of large-size high-performance sintered neodymium-iron-boron magnet

By stacking the layered structure of NdFeB powder and diffusion source powder in the press-forming stage of NdFeB magnets and performing multiple grain boundary diffusion treatments, the problem of insufficient coercive force of large-sized magnets is solved, and high-performance Preparation of large-size NdFeB magnets.

CN119446698APending Publication Date: 2025-02-14JIANGXI COPPER TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411383220.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the coercive force of large-size neodymium iron boron magnets, resulting in poor diffusion effect and cannot be applied to fields where larger-size magnets are needed.

Method used

By mixing the NdFeB powder with the diffusion source powder in the pressing stage to form a diffusion intermediate layer, stacking it into a layered structure, and performing the first and second grain boundary diffusion treatments during the sintering process, the diffusion channel of the diffusion matrix is ​​optimized. and diffusion depth of diffusion source.

Benefits of technology

It realizes high coercive force of large-size NdFeB magnets, has excellent squareness and small residual magnetic loss, and is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119446698A_ABST
    Figure CN119446698A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of neodymium-iron-boron magnetic materials, in particular to a preparation method of a large-size high-performance sintered neodymium-iron-boron magnet. According to the method, a blank of a layered structure is prepared by stacking magnetic powder with different components in a profiling stage, first grain boundary diffusion is accompanied in the sintering process, and then the large-size high-performance sintered neodymium-iron-boron magnet is prepared through traditional grain boundary diffusion (second time). The first grain boundary diffusion involved in the method is generated in the liquid phase sintering densification process, and concentration gradient diffusion is carried out along the grain boundary after a diffusion source is liquefied; and the second grain boundary diffusion is the concentration gradient diffusion of the heavy rare earth on the surface of the compact magnet towards the interior of the magnet. In a large-size magnet, the layered structure design is matched with the twice grain boundary diffusion technology, and the defect of insufficient depth in the traditional grain boundary diffusion technology can be overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of NdFeB magnetic materials, and in particular to a method for preparing a large-size, high-performance sintered NdFeB magnet. Background Art

[0002] High coercivity rare earth permanent magnet materials are widely used in new energy vehicles, variable frequency air conditioners, wind turbines, maglev trains and other technical fields. The larger the magnetocrystalline anisotropy field of the permanent magnet material, the higher the coercivity potential of the material. At the same time, the coercivity of the permanent magnet material is also related to its own microstructure, such as grain size, grain boundary structure and distribution. High magnetocrystalline anisotropy field and good microstructure are prerequisites for high coercivity permanent magnet materials.

[0003] Grain boundary diffusion is one of the important methods to improve the coercivity of magnets. However, grain boundary diffusion technology can only be used to prepare small-sized high-performance magnets. The introduction of heavy rare earth elements such as terbium and dysprosium into the matrix often leads to enrichment on the surface of the magnet, resulting in waste of heavy rare earth elements and loss of magnet performance. In addition, heavy rare earths such as terbium and dysprosium are expensive and are rare and non-renewable resources. Therefore, how to efficiently utilize the amount of heavy rare earths and improve the effective utilization rate of heavy rare earth elements in large-sized magnets has become a hot topic that has attracted much attention.

[0004] The principle of grain boundary diffusion is to attach a diffusion source containing heavy rare earths such as terbium and dysprosium to the surface of the magnet, and introduce the diffusion source into the magnet grain boundary and into the edge of the main phase grain under appropriate heat treatment conditions to obtain a continuous grain boundary and a higher magnetocrystalline anisotropy field, thereby achieving the purpose of improving the coercive force of the magnet. However, in the process of introducing the diffusion source into the magnet, the diffusion depth is shallow due to insufficient diffusion driving force and limited diffusion channels, resulting in poor diffusion effect of large-sized magnets, and cannot be used in fields such as wind power that require larger-sized magnets.

[0005] Therefore, inventing a grain boundary diffusion technology that can be applied to larger-sized magnets, optimizing the diffusion channel of the diffusion matrix, increasing the diffusion depth of the diffusion source, and enhancing the coercive force of larger-sized magnets are of far-reaching significance for promoting the application of rare earth permanent magnets in various fields. Summary of the invention

[0006] The invention discloses a method for preparing a large-size high-performance sintered NdFeB magnet to solve any of the above and other potential problems in the prior art.

[0007] In order to solve the above technical problems, the technical solution of the present invention is: a method for preparing a large-size high-performance sintered NdFeB magnet, the preparation method specifically comprising the following steps:

[0008] S1) mixing NdFeB powder and diffusion source powder to form a diffusion intermediate layer, stacking into a layered structure in the order of NdFeB powder-diffusion intermediate layer-NdFeB powder in a pressing stage, and obtaining a green body with a layered structure after magnetic field molding;

[0009] S2) sintering and densifying the green body obtained in S1), accompanied by a first grain boundary diffusion treatment, to obtain a large-sized diffusion matrix;

[0010] S3) placing another layer of diffusion source on the surface of the large-sized diffusion substrate obtained in S2) and performing a second grain boundary diffusion treatment to obtain a large-sized high-performance sintered NdFeB magnet.

[0011] Further, the chemical composition of the diffusion source in S1) is HRE x RE y M z , wherein HRE is at least one of the heavy rare earths Dy or Tb, RE is at least one of Pr or Nd, M is one or more of Al, Cu, Sn, Ga, In, Nb, Fe, Co and Gd, and x, y and z are mass percentages in the following ranges: x is 50 to 100%, y is 0 to 50%, and x+y+z=100%.

[0012] Furthermore, the particle size of the diffusion source powder is 2-5 μm, and the mass of the diffusion source accounts for 1-10% of the mass of the diffusion intermediate layer.

[0013] Furthermore, the layer structure has an odd number of layers, the thickness of the NdFeB powder layer is 4 to 10 mm, and the stacking thickness direction is the c-axis direction of the magnet.

[0014] Furthermore, the process parameters of the first grain boundary diffusion in S2) are specifically:

[0015] The vacuum degree during sintering is less than 1×10 -2 Pa, the temperature is 1000-1100 ° C, the time is 4-24 h, and then quickly cooled to 20 ° C in an argon atmosphere.

[0016] Furthermore, the process parameters of the second grain boundary diffusion in S3) are as follows: the vacuum degree of the sintering process is less than 1×10 -2 Pa, the temperature is 800-1000°C, the time is 4-48h, and then quickly cooled to 20°C under argon atmosphere.

[0017] Furthermore, the large-sized high-performance sintered NdFeB magnet has non-ferromagnetic RE a Fe b M cphase, wherein RE is one or more combinations of Pr, Nd, Dy, Tb, La, Ce, and Y, and M is one or more combinations of Ga, Co, Al, Cu, Zr, Ni, and Zn; a, b, and c are atomic percentages, a is 1 to 99%, b is 1 to 20%, and c is 1 to 20%.

[0018] Furthermore, the thickness of the diffusion layer of the large-sized, high-performance sintered NdFeB magnet is 1 to 6 mm.

[0019] The large-sized, high-performance sintered NdFeB magnets prepared by the above-mentioned preparation method are applied in the technical fields of new energy vehicles, variable frequency air conditioners, wind turbines and magnetic levitation trains.

[0020] A large-sized, high-performance sintered NdFeB magnet is prepared by the above-mentioned preparation method.

[0021] The present invention prepares a blank with a layered structure by stacking magnetic powders of different compositions in the pressing stage, accompanies the first grain boundary diffusion during the sintering process, and then prepares a large-sized high-performance sintered NdFeB magnet by conventional grain boundary diffusion (second time). The first grain boundary diffusion involved in the present invention occurs during the liquid phase sintering densification process, and the diffusion source liquefies and diffuses along the grain boundary with a concentration gradient; the second grain boundary diffusion is the concentration gradient diffusion of the heavy rare earth on the surface of the magnet into the interior of the magnet after densification.

[0022] Beneficial technical effects of the present invention: Due to the adoption of the above technical solution, the present invention can overcome the defect of insufficient diffusion depth in the traditional grain boundary diffusion technology through layered structure design and grain boundary diffusion technology, and finally obtain a NdFeB magnet with an easy magnetization direction of more than 10mm, and has excellent squareness and small remanence loss. In large-sized magnets (magnets), the process flow of the present invention is easy to control and suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a flowchart of a method for preparing large-size, high-performance sintered NdFeB.

[0024] Figure 2 Schematic diagram of the diffusion of the magnets of Example 1 and Comparative Example 1.

[0025] Figure 3 Schematic diagram of the diffusion of the magnets of Example 2 and Comparative Example 2. DETAILED DESCRIPTION

[0026] The present invention will be further illustrated below in conjunction with examples and comparative examples. It should be understood that the following specific embodiments are only used to illustrate the features and advantages of the present invention, and are not used to limit the scope of the present invention.

[0027] like Figure 1 As shown, the present invention provides a method for preparing large-size high-performance sintered NdFeB, which specifically comprises the following steps:

[0028] First, NdFeB powder and diffusion source powder are mixed to form a diffusion intermediate layer, and in the pressing stage, NdFeB powder-diffusion intermediate layer-NdFeB powder are stacked in the order of layered structure, and a green body with a layered structure is obtained after magnetic field molding;

[0029] Then, the green body is sintered and densified, accompanied by the first grain boundary diffusion process, to obtain a large-sized diffusion matrix;

[0030] Finally, a layer of diffusion source is placed on the surface of the substrate to carry out a second grain boundary diffusion process to obtain a large-sized, high-performance sintered NdFeB magnet.

[0031] Preferably, the chemical composition of the diffusion source is HRE x RE y M z , wherein HRE is at least one of the heavy rare earths Dy or Tb, RE is at least one of Pr or Nd, M is one or more of Al, Cu, Sn, Ga, In, Nb, Fe, Co and Gd, and in particular, x, y, z are mass percentages in the following ranges: x is 50-100%, y is 0-50%, and x+y+z is 100%.

[0032] Preferably, the particle size of the diffusion source powder is 2-5 μm, and the mass of the diffusion source accounts for 1-10% of the mass of the intermediate layer.

[0033] Preferably, the layered structure has an odd number of layers, each layer has the same thickness of 4 to 10 mm, and the stacking thickness direction is the c-axis direction of the magnet.

[0034] Preferably, the vacuum degree during the sintering process is less than 1×10 -2 Pa, the temperature is 1000-1100 ° C, the time is 4-24 h, and then quickly cooled to 20 ° C in an argon atmosphere.

[0035] Preferably, during the sintering process, the diffusion source melts and diffuses from the middle layer to the upper and lower sides, forming a microstructure in which the grain boundary phase content of the middle layer is higher than that of the magnetic powder layer.

[0036] Preferably, the vacuum degree of the second grain boundary diffusion process is less than 1×10 -2 Pa, the temperature is 800-1000°C, the time is 4-48h, and then quickly cooled to 20°C under argon atmosphere.

[0037] Preferably, during the sintering and the second grain boundary diffusion process, the diffusion source reacts with the grain boundary phase to generate non-ferromagnetic REa Fe b M c phase, wherein RE is one or more combinations of Pr, Nd, Dy, Tb, La, Ce, and Y, and M is one or more combinations of Ga, Co, Al, Cu, Zr, Ni, and Zn; in particular, a, b, and c are atomic percentages, a is 1 to 99%, b is 1 to 20%, and c is 1 to 20%.

[0038] Example 1

[0039] (1) According to the formula (PrNd) 30 Zr 0.2 Al 0.2 Cu 0.1 Co 0.3 Ga 0.4 B 0.95 Fe bal (wt.%) Weigh the metal or alloy, grind it and put it into a quick-setting furnace for melting and belt throwing to obtain quick-setting sheets. Then put the quick-setting sheets into a rotary hydrogen crushing furnace for hydrogen crushing to obtain hydrogen crushing coarse powder. Put the obtained hydrogen crushing coarse powder into a jet mill, set the sorting wheel speed to 5000rpm, and obtain 3±0.2μm NdFeB magnetic powder.

[0040] (2) According to the formula Tb 80 Al 7 Ga 8 Cu 5 (wt.%) weigh the metal or alloy, grind it and put it into a quick-setting furnace for melting and belt throwing to obtain quick-setting sheets. Then put the quick-setting sheets into a rotary hydrogen crushing furnace for hydrogen crushing to obtain hydrogen crushing coarse powder. Put the obtained hydrogen crushing coarse powder into a jet mill, set the sorting wheel speed to 5000rpm, and obtain a diffusion source powder of 3±0.2μm.

[0041] (3) The NdFeB magnetic powder prepared in (1) and the diffusion source magnetic powder prepared in (2) are mixed in a mass ratio of 97:3 to form a diffusion intermediate layer, and five layers are stacked in the order of NdFeB magnetic powder-diffusion intermediate layer-NdFeB magnetic powder to form a layered structure in a pressing stage to prepare a layered green body. The stacking direction is the c-axis direction, and the thickness of each layer is 7 mm.

[0042] (4) The green body obtained in (3) is sintered in a vacuum sintering furnace. The vacuum degree must be less than 1×10 - 2 Pa, large-sized sintered NdFeB magnets were obtained after sintering and densification.

[0043] (5) The upper and lower surfaces of the magnet obtained in (4) are polished clean and coated with a layer of diffusion source powder, and then subjected to diffusion heat treatment at 900°C × 24h in a vacuum sintering furnace. After diffusion, a tempering heat treatment at 500°C × 4h is performed to obtain Example (1).

[0044] Comparative Example 1

[0045] (1) NdFeB magnetic powder and diffusion source magnetic powder were mixed in a mass ratio of 98.8:1.2, and then pressed to prepare a green body with a total thickness of 35 mm.

[0046] (2) The green body obtained in (1) is sintered in a vacuum sintering furnace. The vacuum degree must be less than 1×10 - 2 Pa, large-sized sintered NdFeB magnets were obtained after sintering and densification.

[0047] (3) The upper and lower surfaces of the magnet obtained in (2) are polished clean and coated with a layer of diffusion source powder, and then subjected to diffusion heat treatment at 900°C × 24h in a vacuum sintering furnace. After diffusion, a tempering heat treatment at 500°C × 4h is performed to obtain comparative example (1).

[0048] Table 1 Diffusion magnet properties of Example 1 and Comparative Example 1

[0049] <![CDATA[B r / kGs]]> <![CDATA[H cj / kOe]]> <![CDATA[(BH) max / MGOe]]> <![CDATA[H k / H cj ]]> Example 1 14.20 20.55 50.10 0.943 Comparative Example 1 14.18 18.25 49.52 0.811

[0050] Example 2

[0051] (1) According to the formula (PrNd) 31 Zr 0.1 Al 0.1 Cu 0.15 Co 0.3 Ga 0.1 B 0.96 Fe bal (wt.%) Weigh the metal or alloy, grind it and put it into a quick-setting furnace for melting and belt throwing to obtain quick-setting sheets. Then put the quick-setting sheets into a rotary hydrogen crushing furnace for hydrogen crushing to obtain hydrogen crushing coarse powder. Put the obtained hydrogen crushing coarse powder into a jet mill, set the sorting wheel speed to 5000rpm, and obtain 3±0.2μm NdFeB magnetic powder.

[0052] (2) According to the formula Pr 30 Tb 40 Al 20 Fe 10(wt.%) weigh the metal or alloy, grind it and put it into a quick-setting furnace for melting and belt throwing to obtain quick-setting sheets. Then put the quick-setting sheets into a rotary hydrogen crushing furnace for hydrogen crushing to obtain hydrogen crushing coarse powder. Put the obtained hydrogen crushing coarse powder into a jet mill, set the sorting wheel speed to 5000rpm, and obtain a diffusion source powder of 3±0.2μm.

[0053] (3) The NdFeB magnetic powder prepared in (1) and the diffusion source magnetic powder prepared in (2) are mixed in a mass ratio of 95:5 to form a diffusion intermediate layer, and in the pressing stage, 7 layers are stacked in the order of NdFeB magnetic powder-diffusion intermediate layer-NdFeB magnetic powder to form a layered structure, thereby preparing a layered green body. The stacking direction is the c-axis direction, and the thickness of each layer is 6 mm.

[0054] (4) The green body obtained in (3) is sintered in a vacuum sintering furnace. The vacuum degree must be less than 1×10 - 2 Pa, large-sized sintered NdFeB magnets were obtained after sintering and densification.

[0055] (5) The upper and lower surfaces of the magnet obtained in (4) are polished clean and coated with a layer of diffusion source powder, and then subjected to diffusion heat treatment at 900°C × 24h in a vacuum sintering furnace. After diffusion, a tempering heat treatment at 500°C × 4h is performed to obtain Example (1).

[0056] Comparative Example 2

[0057] (1) NdFeB magnetic powder and diffusion source magnetic powder were mixed in a mass ratio of 97.9:2.1, and then pressed to prepare a green body with a total thickness of 42 mm.

[0058] (2) The green body obtained in (1) is sintered in a vacuum sintering furnace. The vacuum degree must be less than 1×10 - 2 Pa, large-sized sintered NdFeB magnets were obtained after sintering and densification.

[0059] (3) The upper and lower surfaces of the magnet obtained in (2) are polished clean and coated with a layer of diffusion source powder, and then subjected to diffusion heat treatment at 900°C × 24h in a vacuum sintering furnace. After diffusion, a tempering heat treatment at 500°C × 4h is performed to obtain comparative example (1).

[0060] Table 2 Diffusion magnet properties of Example 2 and Comparative Example 2

[0061] <![CDATA[B r / kGs]]> <![CDATA[H cj / kOe]]> <![CDATA[(BH) max / MGOe]]> <![CDATA[H k / H cj ]]> Example 2 13.96 22.71 48.22 0.943 Comparative Example 2 13.88 20.18 46.26 0.732

[0062] Comparing the test data of Example 1 and Comparative Example 1, it is found that the coercive force (H cj ) and squareness (H k / H cj) is better than the comparative example, such as Figure 2 As shown. According to the microstructure observation structure, we also found that the diffusion depth of the embodiment is significantly better than that of the comparative example, which also shows that the diffusion effect of the embodiment is optimized and can promote the diffusion of heavy rare earth elements in the matrix, which is consistent with the performance test results. Further, by comparing the magnetic properties and microstructures of Example 2 and Comparative Example 2, the magnetic properties and microstructure of the embodiment are better than those of the comparative example, as shown in FIG. Figure 3 Therefore, the present invention can increase the diffusion depth of heavy rare earth elements and improve their utilization rate through diffusion sources and corresponding diffusion processes, and prepare large-sized and high-coercivity sintered NdFeB magnets.

[0063] Although the specific implementation methods of the present invention are described above, those skilled in the art should understand that these are only examples, and that various changes or modifications may be made to these implementation methods without departing from the principles and implementations of the present invention. Therefore, the scope of protection of the present invention is limited by the appended claims.

Claims

1. A method for preparing a large-size, high-performance sintered NdFeB magnet, characterized in that: The preparation method specifically comprises the following steps: S1) mixing NdFeB powder and diffusion source powder to form a diffusion intermediate layer, stacking into a layered structure in the order of NdFeB powder-diffusion intermediate layer-NdFeB powder in a pressing stage, and obtaining a green body with a layered structure after magnetic field molding; S2) sintering and densifying the green body obtained in S1), accompanied by a first grain boundary diffusion treatment, to obtain a large-sized diffusion matrix; S3) placing another layer of diffusion source on the surface of the large-sized diffusion substrate obtained in S2) and performing a second grain boundary diffusion treatment to obtain a large-sized high-performance sintered NdFeB magnet.

2. The preparation method according to claim 1, characterized in that: The chemical composition of the diffusion source in S1) is HRE x RE y M z , wherein HRE is at least one of the heavy rare earths Dy or Tb, RE is at least one of Pr or Nd, M is one or more of Al, Cu, Sn, Ga, In, Nb, Fe, Co and Gd, and x, y and z are mass percentages in the following ranges: x is 50 to 100%, y is 0 to 50%, and x+y+z=100%.

3. The preparation method according to claim 1, characterized in that: The particle size of the diffusion source powder is 2-5 μm, and the mass of the diffusion source accounts for 1-10% of the mass of the diffusion intermediate layer.

4. The preparation method according to claim 1, characterized in that: The layer structure has an odd number of layers, the thickness of each NdFeB powder layer is 4-10 mm, and the stacking thickness direction is the c-axis direction of the magnet.

5. The preparation method according to claim 1, characterized in that: The process parameters of the first grain boundary diffusion in S2) are specifically: The vacuum degree during sintering is less than 1×10 -2 Pa, the temperature is 1000-1100 ° C, the time is 4-24 h, and then quickly cooled to 20 ° C in an argon atmosphere.

6. The preparation method according to claim 1, characterized in that: The process parameters of the second grain boundary diffusion in S3) are as follows: the vacuum degree during the sintering process is less than 1×10 -2 Pa, the temperature is 800-1000 °C, the time is 4-48 h, and then quickly cooled to 20 °C under argon atmosphere.

7. The preparation method according to claim 1, characterized in that: The large-sized high-performance sintered NdFeB magnet has non-ferromagnetic RE a Fe b M c phase, wherein RE is one or more combinations of Pr, Nd, Dy, Tb, La, Ce, and Y, and M is one or more combinations of Ga, Co, Al, Cu, Zr, Ni, and Zn; a, b, and c are atomic percentages, a is 1 to 99%, b is 1 to 20%, and c is 1 to 20%.

8. The preparation method according to claim 1, characterized in that: The thickness of the diffusion layer of the large-size high-performance sintered NdFeB magnet is 1 to 6 mm.

9. A large-sized, high-performance sintered NdFeB magnet prepared by the preparation method according to any one of claims 1 to 8 is used in the fields of new energy vehicles, variable frequency air conditioners, wind turbines and maglev trains.

10. A large-sized, high-performance sintered NdFeB magnet, characterized in that: The large-size, high-performance sintered NdFeB magnet is prepared by the preparation method described in any one of claims 1 to 8.

Citation Information

Cited By

  • Neodymium-iron-boron magnet and preparation method thereof

    CN121171773A

  • Neodymium-iron-boron permanent magnet material and preparation method and application thereof

    CN121565675A